Lactobacillus reuteri GMNL-263 reduces hyperlipidaemia and the heart failure process in high-calorie diet-fed induced heart dysfunction in rats. (January 2016) - Liao, Po-Hsiang; Kuo, Wei-Wen; Kuo, Chia-Hua; Yeh, Yu-Lan; Shen, Chia-Yao; Chen, Ya-Hui; Chen, Ray-Jade; Padma, V. Vijaya; Chen, Yi-Hsing; Huang, Chih-Yang
Highlights: High-calorie diet feeding induced plasma and liver lipid up-regulation in rats. High-calorie diet feeding induced cardiac injury and promoted heart failure. Oral Lactobacillus reuteri treatment attenuated high calorie induced cardiac inflammation, hypertrophy and fibrosis. Lactobacillus reuteri regulated plasma lipids and ameliorated high calorie induced heart dysfunction. Abstract: Probiotics are reported to provide protective health benefits against various disorders. In this study, we established a high-calorie diet animal model with a diet prepared by fortifying normal diet with soybean oil and condensed milk and the animals were supplemented with different dose of probiotic Lactobacillus reuteri GMNL-263(Lr263) for 8 weeks to investigate the protective function. We measured the lipid levels in plasma, liver and faecal; heart weight, function and collagen accumulation and biochemical markers of cardiac disease. Lr263 reversed high-calorie diet-induced cardiac weight gain, systolic malfunction and prevented heart inflammation by decreasing inflammation proteins NF-κB and COX-2. Moreover, Lr263 reduced cardiac eccentric hypertrophy and the levels of cardiac fibrosis markers CTGF and SP1 in high-calorie diet-fed rat hearts. Thus, Lr263 is considered as a functional food that provides anti-inflammatory, anti-hypertrophic, anti-fibrotic functions and identified specific biologic effects in reducing the characteristics of the high-calorie diet-induced progression to heart failure.